The Relatiionship between earnings, education, age, and cohort size for Canadian men during the period 1986-2001 - Nguyen, Giang thi-thuy (Université d'Ottawa | University of Ottawa, 2007)
Individual data for Canadian men from Censuses for the years 1986, 1991, 1996 and 2001 are used to re-examine Dooley's (1986) study of changes in the relationships between experience, education, cohort size, and earnings. This study adopted Dooley's (1986